Pack up your worries. (2nd May 2021) - Burch, Victoria
Abstract : Addressing childhood fears and stresses is currently a priority for schools and early years settings. Victoria Burch gives her view on how resources developed by Act International, a charity dealing with childhood trauma, can help.